Wybrane metody wyceny programu emerytalnego o zdefiniowanym świadczeniu - modelowanie wysokości składki i amortyzacja deficytu - Sipa, Magdalena (Selected methods of valuating defined benefit pension plans - modeling the contribution and deficit amortization, 2006)
The valuation of pension plans depends on the calculation of the aggregated capital amount and the mathematical provision at a given moment. On the basis of the obtained results, the contribution amount is established and this amount is applied until the next valuation. The pension plan valuation was conducted on the basis of the constant contribution amount for the whole participation period as well as of the contribution amount correction at every valuation moment. Three methods of deficit amortization and financial surplus were discussed. The author presented the way in which the contribution amount is to be established in order to attain the actuarial balance for the pension plan participation at the final moment. The amount of the aggregated capital was compared with the mathematical provision necessary to cover the benefits at every moment of insurance security. Three methods of deficit amortization (financial surplus) were suggested.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 453-463